The Effect of Dose Herbicide Active Ingredient Metsulfuron methyl on Weed Control, Growth and Yield of Rice Plants (Oryza sativa L.) Inpari 32 varieties - Handayani, Lestari; Kurniasari, Yuni; Abdurrahman Asysyafaat, Alfian; Hambali, Basyir; Deden, Deden; Budirokhman, Dodi (Interdiciplinary Journal and Hummanity (INJURITY), 2023)
Rice (Oryza sativa L) is a food crop commodity that has a major role in the development of agriculture and the main food of the Indonesian people. Rice is a rice-producing crop. Rice (Oryza sativa L) is a food crop commodity that has a major role in the development of agriculture and the main food of the Indonesian people. Rice yield loss due to weeds is estimated at 10 to 15%, even up to 86% without control. The purpose of the study was to determine the effect of herbicide dosage levels and obtain the best dose of the active ingredient Metsulfuron methyl on weed control and rice crop yield (Oryza sativa L.). The experimental method used was an experimental method using Group Randomized Design (RAK) consisting of 7 experimental units and repeated 4 times, so that 28 experimental plots were obtained. The experimental treatment was A (Metsulfuron methyl 15 g / ha, B (Metsulfuron methyl 20 g / ha), C (Metsulfuron methyl 25 g / ha), D (Metsulfuron methyl 30 g / ha), E (Metsulfuron methyl 35 g / ha), F (manual control) and G (control). The results showed that herbicides made from Metsulfuron methyl with doses of 15 g / ha – 35 g / ha had an influence on the population growth of rice weed species such as Cyperus iria, Fimbristylis miliacea and Leptochloa chinensis. Herbicide with active ingredient Metsulfuron methyl does not have a toxic effect on rice plants. Metsulfuron methyl with a treatment dose range from 15 g / ha – 35 g / ha has a significant effect on rice weed control when compared to control treatment. The dose of Metsulfuron methyl is significantly different when compared to all dose levels tested and is able to produce dry rice grain as much as 14.21 kg / plot or equivalent to 22.7 tons / hectare.